Electromagnetic wave diffraction by a cone with longitudinal slots and a solid conic screen inside - Doroshenko, V. A.; Semenova, E. K. (IEEE, 2003)
A numerical-analytical solution of the problem of excitation of an unlimited perfectly conducting biconical surface is considered. Surface consists of both a cone with periodical longitudinal slots and an internal solid conical screen. The effects of slots and solid cone on the Fourier coefficient of the electromagnetic field components and the scattering patterns are discussed. The obtained results are in good agreement with previously recognized ones for solid bicone structure.
Keywords: biconical surface; cone with longitudinal slots